Modern ways to reduced mortality of myocardial infarction. What should be done? - O. L. Barbarash; T. B. Pecherina (Сибирский научный медицинский журнал)
Myocardial infarction is a formidable manifestation of coronary artery disease and accounts for one third of deaths associated with coronary disease. In Russia, from 400 to 500 thousand patients with acute coronary syndrome are hospitalized annually, about half of them with myocardial infarction (MI). The dynamics of the number of hospitalized patients in recent years indicates its reduction. Short-term mortality (30-day, including hospital mortality) after acute MI has decreased significantly over the past 50 years: in absolute terms from 30 % in 1950 to 5–8 % at present. However, long-term mortality after MI did not improve. Moreover, in recent years, the rate of decline in 30-day mortality from MI has decreased significantly, almost reaching a “plateau” over the past 15 years. It has been established that in terms of the impact on survival, disability and quality of life of the working population, MI is an important not only medical but also social problem. This review of the literature discusses changes in approaches to reducing mortality in MI, as well as the main events in evidence-based cardiology over the past 50 years, which have made it possible to effectively manage the risk of death in this category of patients.